Determination of multiple organochlorine pesticide residues in shrimp using modified QuEChERS extraction and gas chromatography - Prodhan, MDH; Alam, SN (SAARC Journal of Agriculture, 2018)
Determination of organochlorine pesticide residues in shrimp is very important to ensure the consumer’s safety and to fulfill the importer’s demand. Therefore, a simple and efficient multiple organochlorine pesticide residues analytical method using quick, easy, cheap, effective, rugged and safe (QuEChERS) extraction technique and Gas Chromatography coupled with Electron Capture Detector (ECD) has been developed and validated for the determination of 19 organochlorine pesticides (α- BHC, δ- BHC, β- BHC, γ- BHC, Heptachlor, Aldrin, Heptachlor Epoxide, γ- Chlordane, α- Chlordane, α- Endosulfan, 4,4 DDE, Dieldrin, Endrin, 4,4 DDD, β- Endosulfan, 4,4 DDT, Endosulfan sulphate, Methoxychlor, and Endrin Ketone) in shrimp. The method was validated by evaluating the accuracy, precision, linearity, limit of detection (LOD) and limit of quantification (LOQ). The average recoveries of the selected pesticides ranged from 84% to 106% with RSDr ≤ 14% in four fortification levels of 0.05, 0.1, 0.2 and 0.3 mg kg-1. The linearity was ≥ 0.996 for all of the selected pesticides with matrix matched calibration standards. The LOD ranged from 0.003 to 0.009 mg kg-1 and the LOQ was 0.05 mg kg-1. This method was applied successfully for the residue analysis of 40 shrimp samples collected from different regions in Bangladesh. SAARC J. Agri., 16(1): 81-93 (2018)